Analytical and Numerical Approaches for Design of Stone Pavers in Urban Shared Areas. Issue 6 (February 2019) - Loprencipe, Giuseppe; Mascio, Paola Di; Moretti, Laura; Zoccali, Pablo
Abstract: Existing statistical data show that the use of pedestrian block pavements is increasing. This paper compares two approaches used to analyse a block pavement in an urban shared area. In presence of occasional heavy traffic roads, the pavement should be verified using methods currently used for road pavements. The analytical theory of Westergaard and the commercial finite element (FE) software Abaqus® were used to calculate the response of the pavement when subjected to different loading, and geometrical configurations. In all the examined cases, the results obtained from the analytical theory of Westergaard were higher than those obtained from the adopted static FEMs. Therefore, a parametric study was performed in order to use the analytical method as an alternative to the costly FEM approach introducing a Dynamic Amplification Factor (DAF). The results of comparison gave interesting results, valid for hexagonal pavers: it is possible to estimate analytically with good approximation the stresses induced by heavy loads applied to natural stone blocks. This is an interesting result since the analytical theory provides an inexpensive procedure for the analysis of modular pavements.